2022
DOI: 10.3390/ijerph19053048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Single and Multi-LED Emitters for Photodynamic Therapy: An In Vitro Study on Enterococcus faecalis and Human Gingival Fibroblasts

Abstract: Aim of the study: The aim was to evaluate the effects of two LED devices, TL-01 and TL-03 in photodynamic therapy (PDT), on Enterococcus faecalis and on human gingival fibroblasts (HGFs). TL-01, characterized by a single emitter, irradiates one periodontal site at a time, whereas the multi-led device (TL-03) irradiates all vestibular sites of a single arch at a time. Methods: E. faecalis bacterial suspensions and HGFs were incubated for 45 min with Aladent gel (ALAD) containing 5-aminolevulinic acid and then e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 21 publications
(32 reference statements)
0
27
1
Order By: Relevance
“…The microbial population decreased, indicating a growth inhibition effect versus the control, without a killing action. Instead, remarkable cell death was detected in presence of ala. As demonstrated by Petrini et al [28], the gel could englobe and suffocate the cells most susceptible to the treatment.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The microbial population decreased, indicating a growth inhibition effect versus the control, without a killing action. Instead, remarkable cell death was detected in presence of ala. As demonstrated by Petrini et al [28], the gel could englobe and suffocate the cells most susceptible to the treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, PpIX, under irradiation, serves as an in situ photosensitizer, leading to bacterial inactivation [27]. In an in vitro study, Petrini et al [28] demonstrated the increase in fluorescence of PpIX after the addition of ALAD gel to E. faecalis solution and after the LED irradiation, the endogenous PpIX produced remarkable cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results of in vitro and in vivo studies concerning the ALAD-PDT protocol applied to treat oral infections by killing microbes [ 10 , 11 , 12 , 15 ] drove us to test the same protocol to investigate whether ALAD-PDT may have some effects on cell populations of the oral cavity such as gingival fibroblasts and oral osteoblasts derived from human biopsies.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the 630 nm light irradiation of cells with an increased accumulation of PpIX promotes a highly selective production of ROS, and decreased levels of mitochondrial membrane potential, which induces cell death by both apoptosis and necrosis without damaging the surrounding healthy cells [ 9 ]. The ability of ALAD-PDT to inactivate both Gram-positive and -negative bacteria has been shown in different in vitro studies [ 10 , 11 , 12 ]. ALAD-PDT is effective for biofilm removal from different titanium surfaces, showing encouraging results against peri-implantitis and chronic wounds [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%